P147 An audit into the optimum time for neisseria gonorrhoeae test of cure following treatment in sexual health centres. (8th June 2017) - Slack, Daniel; Gilson, Rebecca
Abstract : Introduction: Neisseria gonorrhoeae is the second most common bacterial sexually transmitted infection worldwide and has evolved resistance to several antibiotic classes. BASHH Guidelines 2011 currently recommend ceftriaxone 500mg IM plus azithromycin 1g stat as first line treatment and also recommend a test of cure (TOC) at 14 days. In our centre the time period between treatment and TOC was reduced to 14 days in July 2016. Anecdotal evidence suggests that this may be producing a higher false positive rate. Methods: Clinical notes for all positive gonorrhoea tests (pharyngeal, rectal, urethral, cervical) in a 3-month period were reviewed. Positive TOC were identified and reasons for these assessed (reinfection, treatment failure, false positive). Cycle threshold (CT) values were used to help identify false positives. Results: 7.5% of TOC results performed at 14 days were likely false positive (no risk of reinfection or treatment failure, high CT values), compared with 2.7% of TOC performed after 14 days. 8.3% of pharyngeal samples and 12.5% of urinary samples were false positive. There were no false positives found for rectal and vulvovaginal samples. Discussion: There is a significantly higher rate of false positives when a TOC is performed at 14 days and they are more prevalent in pharyngeal and urinary samples. This has a negative impact on both patient and health care provider time and can lead to unnecessary retreatment. Potential interventions could be to extend the TOC time period, include CT values for all TOC results or move to a less sensitive NAAT for TOC.